The impact of social capital and technological uncertainty on strategic performance: The supplier perspective. Issue 3 (September 2016) - Gelderman, Cees J.; Semeijn, Janjaap; Mertschuweit, Patrique P.
Abstract: Social capital is a valuable asset for companies that stems from access to resources made available through buyer-supplier relationships. Many studies have investigated the antecedents and/or the impact of cognitive, relational, and structural dimensions of social capital on some performance measure. Our study extends this research by considering the moderating effect of technological uncertainty on the relation between social capital dimensions and the strategic performance of suppliers. A sample of 88 European industrial suppliers is used to test the hypotheses. Analysis shows a positive, significant impact of cognitive social capital, but failed to confirm the expected influence of the relational and structural dimensions. No moderator effects were found in the analysis, although we did find a positive association between technological uncertainty and strategic performance. This finding suggests that technological uncertainty can stimulate suppliers to develop new products and to enter new markets. Highlights: We studied the impact of social capital dimensions from a supplier perspective. Cognitive social capital positively relates to strategic performance. Technological uncertainty directly impacts strategic performance. Relational social capital is associated with cognitive and structural social capital. Social capital theory appears to be highly relevant in buyer-supplier relationships.